2015
DOI: 10.3171/2015.1.jns141452
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radiation-induced cavernous malformations and comparison with a nonradiation cavernous malformation cohort

Abstract: abbreviatioNs CM = cavernous malformation; GRE = gradient echo; mRS = modified Rankin Scale; RICM = radiation-induced CM; RIT = radiation-induced telangiectasia; SWI = susceptibility-weighted imaging. results Thirty-two patients with RICMs were identified (56.2% men), with a median age of 31.1 years at RICM diagnosis. The median latency from radiation treatment to RICM diagnosis was 12.0 years (interquartile range 5.0-19.6 years). RICMs were always within the previous radiation port. RICMs were symptomatic at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 37 publications
(31 reference statements)
1
60
1
Order By: Relevance
“…Moreover, both clinical reports and experiments in animal models have raised the possibility that the ‘second hit’ may not be limited to genetic disruptions but could also take the form of recurrent exposure of the particularly sensitive brain vasculature to local cellular stresses (Jung et al, 2003, Leblanc et al, 2009, Whitehead et al, 2009). Accordingly, it has been reported that CCM3 mouse mutants only develop lesions in conjunction with severe astrocytosis at the lesion site, suggesting that injury of astrocytes may play a role in lesion formation (Louvi et al, 2011), a notion consistent with clinical reports of CCM developing or expanding after physical trauma, injury, or radiation (Cutsforth-Gregory et al, 2015, Louvi et al, 2011). Furthermore and importantly, the development of CCM lesions induced by endothelial-specific conditional knockout of CCM genes in neonatal mice is highly restricted, both spatially and temporally, despite the pan-endothelial deletion of CCM genes (Boulday et al, 2011, Chan et al, 2011, Gibson et al, 2015, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, both clinical reports and experiments in animal models have raised the possibility that the ‘second hit’ may not be limited to genetic disruptions but could also take the form of recurrent exposure of the particularly sensitive brain vasculature to local cellular stresses (Jung et al, 2003, Leblanc et al, 2009, Whitehead et al, 2009). Accordingly, it has been reported that CCM3 mouse mutants only develop lesions in conjunction with severe astrocytosis at the lesion site, suggesting that injury of astrocytes may play a role in lesion formation (Louvi et al, 2011), a notion consistent with clinical reports of CCM developing or expanding after physical trauma, injury, or radiation (Cutsforth-Gregory et al, 2015, Louvi et al, 2011). Furthermore and importantly, the development of CCM lesions induced by endothelial-specific conditional knockout of CCM genes in neonatal mice is highly restricted, both spatially and temporally, despite the pan-endothelial deletion of CCM genes (Boulday et al, 2011, Chan et al, 2011, Gibson et al, 2015, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 57%
“…Second, loss of endothelial cell-cell contact, even in heterozygous patients and animals, would likely predispose the vasculature to chronic, low-grade inflammation due to intermittent exposure of the vascular basement membrane, a potent inflammatory stimulus (Mackel et al, 1982). A related example of such a mechanism is observed in radiation-induced cavernous malformation (RICM) in which radiation-induced endothelial damage leads to the stimulation of pro-inflammatory signaling, the development of large, often multiple, vascular malformations that closely resemble CCMs, and hemorrhage (Cutsforth-Gregory et al, 2015, Nimjee et al, 2006, Park et al, 2011). Third, recent evidence suggests that innate immune cells contribute to the vascular permeability phenotype of KRIT1 deficient mice.…”
Section: Role Of Inflammation In Ccm Pathogenesismentioning
confidence: 99%
“…Previous studies demonstrated that 6–44% of patients with cerebral RICHs are symptomatic at diagnosis . By contrast, six of the seven cases with intraspinal RICHs were diagnosed by neurological symptoms and four cases out of the seven needed surgical interventions.…”
Section: Discussionmentioning
confidence: 89%
“…Since Cirricillo et al. reported seven patients in 1994, more than 100 cases with radiation‐induced cavernous hemangiomas (RICHs) have been described . Of note, annual screening of cranial magnetic resonance imaging (MRI) demonstrated that up to 41.2% of pediatric and young adult patients with cranial radiotherapy developed cerebral RICHs after hematopoietic stem cell transplantation (HSCT) .…”
Section: Introductionmentioning
confidence: 99%
“…Female gender, male gender, patient age, associated edema, size, deep location, and multiplicity of cavernous malformations have been found to increase the risk of bleeding and these factors are variable dispersed and reported among studies [4, 5,10,13,18,19,21,22,29-31]. Furthermore, the risks in familial and radiation-induced cavernous malformations may differ from congenital and spontaneous lesions [10,17,32].…”
mentioning
confidence: 99%